Inventory management strategies propensity toward supply chain management in the aerospace industry in Malaysia : the moderating effect of financial risk consideration - Khor, Wei Min (2017)
This thesis examined the relationship between inventory management strategies (IMS) and supply chain management (SCM) performance in the aerospace industry, an advanced and high technology industry that is characterized by a high working capital with potential huge losses if something goes wrong. The IMS dimensions of stock holding, safety stock, storage policy and inventory risk were tested against the SCM performance dimensions of on-time delivery (OTD), balance score card (BSC), inventory turn and factors related to inventory-financial risks. The quantitative research methodology was opted for this study. Data collection was performed from January to May 2016, involving 81 respondents related to the aerospace industry in Malaysia. This accounted for 40.5% of the population in the country. The Statistical Package for the Social Sciences (SPSS) was used to assist in the analysis. The findings indicated that only two dimensions of the IMS are used as predictors for the SCM performance. It also revealed that every dimension of the SCM performance is significant with only one dimension of the IMS. The most important dimension of SCM performance is the inventory risk dimension. Contrary to the initial expectation, storage policy is found to be insignificant for the theoretical relationship in this industry and the financial risk factor is found to be a weak moderator in the proposed relationship. The findings also suggested the need to examine financial risk consideration as the independent variable when examining the SCM performance in the aerospace industry. Moreover, these findings can be considered unique as they offer different contributing dimensions to the SCM performance and these should be the eye-opener to the organizations that have different attributes, in particular the high technology industry that involves high working capital.